(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In 1880 Narendra joined Keshab Chandra Sen’s Nava Vidhan, which was established by Sen after meeting Ramakrishna and reconverting from Christianity to Hinduism. Narendra became a member of a Freemasonry lodge at some point before 1884 and of the Sadharan Brahmo Samaj in his twenties, a breakaway faction of the Brahmo Samaj led by Keshab Chandra Sen and Debendranath Tagore. From 1881 to 1884 he was also active in Sen’s Band of Hope, which tried to discourage youths from smoking and drinking. It was in this cultic milieu that Narendra became acquainted with Western esotericism. His initial beliefs were shaped by Brahmo concepts, which included belief in a formless God and the deprecation of idolatry and a streamlined, rationalized, monotheistic theology strongly coloured by a selective and modernistic reading of the Upanisads and of the Vedanta.